2015
DOI: 10.1107/s1600576715002976
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the melting and freezing temperatures of Pb nanoparticles embedded in a PbO–B2O3–SnO2glass by using only the SAXS method

Abstract: Melting and freezing of metallic nanoparticles embedded in glass matrices usually occur at temperatures lower than for the same metal in the bulk state. In situ small-angle X-ray scattering (SAXS) measurements using a synchrotron beamline and a specially designed high-temperature chamber allowed the determination of the temperature dependence of the SAXS intensity produced by a dilute and nearly monodisperse set of spherical Pb nanoparticles, with an average radius hRi = 16.1 nm, embedded in a homogeneous lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…As established in a previous study of a set of spherical Pb nanoparticles with a narrow radius distribution embedded in glass (Kellermann et al, 2015), precise determination of transition temperatures was achieved by only analysing Q(T) functions derived from experimental SAXS patterns. For the previously studied Pb-glass composites (Kellermann et al, 2015) the Q(T) functions actually exhibit sharp jumps at the transitions, this behaviour being expected for systems of nanoparticles with narrow size distributions. On the other hand, for the glass samples containing Bi nanoparticles studied here, smooth variations in Q(T) at the transition temperatures are observed in the different hysteresis loops displayed in Figs.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…As established in a previous study of a set of spherical Pb nanoparticles with a narrow radius distribution embedded in glass (Kellermann et al, 2015), precise determination of transition temperatures was achieved by only analysing Q(T) functions derived from experimental SAXS patterns. For the previously studied Pb-glass composites (Kellermann et al, 2015) the Q(T) functions actually exhibit sharp jumps at the transitions, this behaviour being expected for systems of nanoparticles with narrow size distributions. On the other hand, for the glass samples containing Bi nanoparticles studied here, smooth variations in Q(T) at the transition temperatures are observed in the different hysteresis loops displayed in Figs.…”
Section: Figurementioning
confidence: 99%
“…A number of nanostructured materials with interesting optical properties are composed of a homogeneous glass matrix in which dilute sets of metallic (Uchida et al, 1994;Itoigawa et al, 1997;, 2003, 2008Kellermann et al, 2015) or semiconductor (Borelli et al, 1987;Liu & Risbud, 1990;Medeiros Neto et al, 1991;Craievich et al, 1997Craievich et al, , 2002 nanoparticles are embedded. These doped glasses exhibit interesting optical properties with potential applications in photonics (Barbosa et al, 1995;Olivares et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A determination of the melting and freezing temperatures of Pb nanoparticles embedded in a lead borate glass was previously performed by combined use of SAXS, TEM and electron diffraction (Kellermann et al, 2015). The TEM and electron diffraction analyses of that material at room temperature demonstrated that the observed nanoparticles are Pb nanocrystals with face-centered cubic crystallographic lattice and nearly the same lattice parameter as bulk Pb.…”
Section: Tem Analysismentioning
confidence: 99%
“…The TEM and electron diffraction analyses of that material at room temperature demonstrated that the observed nanoparticles are Pb nanocrystals with face-centered cubic crystallographic lattice and nearly the same lattice parameter as bulk Pb. In the present study, quenched (initially nearly homogeneous) samples of the same material as another studied before (Kellermann et al, 2015) were annealed for 120 min at 649 K and then observed by TEM at room temperature in order to establish the nature, shape and size of the precipitated Pb nanoparticles embedded in the glass matrix. The TEM images displayed in Figs.…”
Section: Tem Analysismentioning
confidence: 99%